Brain Stimulation as a Therapeutic Tool in Amyotrophic Lateral Sclerosis: Current Status and Interaction With Mechanisms of Altered Cortical Excitability - Ranieri, Federico; Mariotto, Sara; Dubbioso, Raffaele; Di Lazzaro, Vincenzo (Frontiers in Neurology, 2021)
In the last twenty years several modalities of neuromodulation, mainly based on non-invasive brain stimulation (NIBS) techniques, have been tested as a non-pharmacological therapeutic approach to slow disease progression in amyotrophic lateral sclerosis (ALS). In both sporadic and familial ALS cases, neurophysiological studies point to motor cortical hyperexcitability as a possible priming factor in neurodegeneration, likely related to dysfunction of both excitatory and inhibitory mechanisms. A trans-synaptic anterograde mechanism of excitotoxicity is thus postulated, causing upper and lower motor neuron degeneration. Specifically, motor neuron hyperexcitability and hyperactivity are attributed to intrinsic cell abnormalities related to altered ion homeostasis, and to impaired glutamate and GABA signaling. Several neuropathological mechanisms support excitatory and synaptic dysfunction in ALS; additionally, hyperexcitability seems to drive TDP-43 pathology, through the upregulation of unusual isoforms directly contributing to ASL pathophysiology. Corticospinal excitability can be suppressed or enhanced using NIBS techniques, namely repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), as well as invasive brain and spinal stimulation. Experimental evidence supports the hypothesis that the after-effects of NIBS are mediated by LTP-/LTD-like mechanisms of modulation of synaptic activity, with different biological and physiological mechanisms underlying the effects of tDCS and rTMS and, possibly, of different rTMS protocols. This potential has led to several small trials testing different stimulation interventions to antagonize excitotoxicity in ALS. Overall, these studies suggest a possible efficacy of neuromodulation in determining a slight reduction of disease progression, related to the type, duration, and frequency of treatment, but current evidence remains preliminary. Main limitations are the small number and heterogeneity of recruited patients, the limited “dosage” of brain stimulation that can be delivered in the hospital setting, the lack of a sufficient knowledge on the excitatory and inhibitory mechanisms targeted by specific stimulation interventions, and the persistent uncertainty on the key pathophysiological processes leading to motor neuron loss. Present review article provides an update on the state of the art of neuromodulation in ALS, and a critical appraisal of the rationale for the application/optimization of brain stimulation interventions, in the light of their interaction with ALS pathophysiological mechanisms.